Bangladesh: from counting the poor to making the poor count. - The World Bank; World Bank. (Washington, D.C. : World Bank, 1999)
This report is a part of a process of strengthening capacity and enhancing poverty data and analysis in Bangladesh.
Includes bibliographical references (p. [61]-66).
osc 04/08/16
Loans
Keywords: Poor; Poverty; Bangladesh